Association of factor expression levels with health-related quality of life and direct medical costs for people with haemophilia B. (31st December 2022) - Burke, Tom; Shaikh, Anum; Ali, Talaha M.; Li, Nanxin; Curtis, Randall; Garcia Diego, Daniel-Anibal; Recht, Michael; Sannie, Thomas; Skinner, Mark; O'Hara, Jamie
Abstract: Aims: Gene therapy trials aim to provide a functional cure for patients with haemophilia B (HB), and treatment impact is analyzed by factor IX expression levels (FELs). We investigated the relationship of FELs with health-related quality of life (HRQoL) and costs. Materials and methods: This was a retrospective cross-sectional analysis of the European (CHESS I-II) and US (CHESS-US) CHESS population studies. Physicians recruited consecutive patients and extracted information from the medical records; patients completed questionnaires between 2014 and 2015 (CHESS-I), 2018–2019 (CHESS-II) and 2019 (CHESS US). Patients with inhibitors were excluded. HRQoL was assessed using the EQ-5D-5L. Twelve-month haemophilia-related direct medical costs included office visits and hospitalizations based on country-level unit costs. A Tobit model was used to analyze FELs and HRQoL and generalized linear models for direct medical costs. Results: A total of 191 men with HB completed the EQ-5D questionnaire; the mean age was 36.8 years, with a mean FEL of 10.1 IU/dL (median, 4.0). Mean EQ-5D was 0.77 (SD, 0.23). The Tobit model adjusting for age, body mass index and blood-borne viruses showed every 1% increase in FEL was associated with +0.006 points in the mean EQ-5D score ( p = .003). Mean haemophilia-related direct medical costs excluding factor replacement therapy were €2, 028/year (median, €919) in CHESS I-II (EU, n = 226), and 7, 171/year (median, 586) in CHESS US ( n = 181). Adjusted EU and US models showed every 1% increase in FEL was associated with a decrease in haemophilia-related direct medical costs of €108/year and 529/year, respectively. Limitations: Direct medical costs were based on physician extraction of encounters from medical records, potentially underestimating costs of care. The voluntary nature of participation may have introduced selection biases. Conclusions: We observed a significant association of increases in FEL with increased HRQoL and decreased costs in Europe and the United States among men with HB and no inhibitors.